Supported Employment, Participation at Work, and Peer Support: A Qualitative, Participatory Case Study Report of the Geesthacht Model - von Peter, Sebastian; Göppert, Lena; Ziegenhagen, Jenny; Beeker, Timo; Glück, Rosa; Groth, Birte; Groß, Uwe; Reinholdt, Arne; Boerma, Robin; Heißler, Matthias; Habicht, Juri; Schwarz, Julian (Frontiers in Psychiatry, 2021)
Background: For people who have experienced mental health crises or psychosocial disabilities, it is considerably more difficult to receive support to participate in work on an equal basis with others. In the town of Geesthacht, in Northern Germany, an integrative care network was implemented that allows for acute psychiatric treatment as well as participation in work and activities. This paper aims to explore the principles, advantages, and challenges of this innovative project. Methodology: Within the context of a participatory and collaborative process evaluation of a prospective controlled cohort study (PsychCare), researchers with and without experiential expertise conducted expert interviews and focus groups to evaluate the experiences of 37 employees, with and without lived experience, from various institutions associated with this care network. The data was analyzed using qualitative content analysis. Results: It was the change from financial compensation paid on a daily basis to a global treatment budget that allowed for a significant reduction of hospital beds in Geesthacht and freed up resources to implement a complex care network. Since then, various possibilities for participation, work, and activities for former service users, some of which are compensated financially, have been made available. These developments now allow for a less bureaucratic and often smooth transition from being a service user to involvement in participatory activities in the role of a peer, which is frequently perceived to be empowering and beneficial by participants with lived experience. At the same time, this care model has led to multiple role conflicts and different challenges for all parties involved. Conclusion: This innovative project in Geesthacht demonstrates the multifaceted potential of a global treatment budget system in the field of mental health care. To address certain downsides of the Geesthacht model, further development is necessary.